Jason’s cloak in Apollonius Argonautica - Alexandra Sousa (Karanos)
Jason’s shining arrival at Myrine, in Apollonius’ Argonautica, wearing a purple cloak and with a spear in the hand, highlights a glamorous heroic excellence that has its origin in Alexander the Great and evokes the military ceremonial mantles displayed during the Ptolemaic processions. Jason is so seductive that the Lemnian women feel ravished at his sight. He evokes Achilles at the gates of Troy sparkling with his armour (Il. 22.25-32). But the battlefield will be the bed in women’s arms. He and almost all of his crew are going to be married to the Lemnians, just as Alexander and his officers did at Susa in 324 BCE. Through a literary resource cherished by Hellenistic poets, an ecphrasis, Apollonius challenges the epic canon, suggesting readings that merge fiction with historical facts, through two opposite cosmic forces φιλότης and νεῖκος. The seven scenes embroidered in the cloak embody them in its tension. Aphrodite, who holds the shield of Ares and sees herself on it, represents those two forces that give the plot, as well as history, its dynamics.